Optoelectronic Enhancement of Perovskite Solar Cells through the Incorporation of Plasmonic Particles - Saheed, M.S.M. (MDPI, 2022)
The optoelectronic advantages of anchoring plasmonic silver and copper particles and non-plasmonic titanium particles onto zinc oxide (ZnO) nanoflower (NF) scaffolds for the fabrication of perovskite solar cells (PSCs) are addressed in this article. The metallic particles were sputter-deposited as a function of sputtering time to vary their size on solution-grown ZnO NFs on which methylammonium lead iodide perovskite was crystallized in a controlled environment. Optical absorption measurements showed impressive improvements in the light-harvesting efficiency (LHE) of the devices using silver nanoparticles and some concentrations of copper, whereas the LHE was relatively lower in devices used titanium than in a control device without any metallic particles. Fully functional PSCs were fabricated using the plasmonic and non-plasmonic metallic film-deco-rated ZnO NFs. Several fold enhancements in photoconversion efficiency were achieved in the sil-ver-containing devices compared with the control device, which was accompanied by an increase in the photocurrent density, photovoltage, and fill factor. To understand the plasmonic effects in the photoanode, the LHE, photo-current density, photovoltage, photoluminescence, incident pho-ton-to-current conversion efficiency, and electrochemical impedance properties were thoroughly investigated. This research showcases the efficacy of the addition of plasmonic particles onto photo anodes, which leads to improved light scattering, better charge separation, and reduced electronâ hole recombination rate. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.